Which site is better for prophylactic ileostomy after laparoscopic rectal cancer surgery? By the specimen extraction site or new site: A systematic review and meta-analysis - Zheng, Bobo; Wang, Quan; Wei, Mingtian; Yue, Yumin; Li, Xiaojun (Frontiers in Oncology, 2023)
Background There is controversy about the outcomes of prophylactic ileostomy via the specimen extraction site (SES) after laparoscopic rectal cancer surgery (LRCS). We, therefore, performed a meta-analysis to determine the efficacy and safety of stoma through the SES versus new site (NS). Methods All relevant studies from 1997 to 2022 were searched in the PubMed, EMBASE, Cochrane Library, CNKI, VIP databases. This meta-analysis was performed using RevMan software 5.3 for statistical analysis. Results 7 studies with 1736 patients were included. The present meta-analysis noted that prophylactic ileostomy via SES was associated with a higher risk of overall stoma-related complications, especially parastomal hernia (OR, 2.39, 95% CI 1.43-4.00; p=0.0008). No statistical difference was found in terms of wound infection, ileus, stoma edema, stoma prolapse, stoma necrosis, stoma infection, stoma bleeding, stoma stenosis, skin inflammation around the stoma, stoma retraction and postoperative pain score on postoperative day 1 and 3 between SES group and NS group. However, prophylactic ileostomy via SES was associated with lesser blood loss (MD = -0.38, 95% CI: -0.62 - -0.13; p=0.003), shorter operation time(MD = -0.43, 95% CI: -0.54 - -0.32 min; p<0.00001), shorter post-operative hospital stay(MD = -0.26, 95% CI: -0.43 - -0.08; p=0.004), shorter time to first flatus(MD = -0.23, 95% CI: -0.39 - -0.08; p=0.003) and lower postoperative pain score on postoperative day 2. Conclusion Prophylactic ileostomy via SES after LRCS reduces new incision, decreases operative time, promotes postoperative recovery, and improves cosmetic outcomes, but may increase the incidence of parastomal hernias. The vast majority of parastomal hernias can be repaired by closing the ileostomy, therefore SES remain an option for temporary ileostomy after LRCS.